Prevalence of Injuries in Rugby League Players in Antioquia and possible correlated factors - Mesa, Juan Felipe Correa; Morales, Juan Carlos Correa; Cardona, Manuela Marín (Journal of Posthumanism, 2024)
Rugby is a contact sport known for its high intensity and physical demands. Due to the physical nature of the game, there is a high prevalence of injuries worldwide. This study aims to estimate the prevalence of injuries among rugby players from the Colombian Federation and to identify potential correlated factors.This is a quantitative, observational, descriptive-correlational study with a cross-sectional design. The target population consisted of active rugby players from the Colombian Federation. The sample includes 80 players, of whom 62% (49) are men and 38% (31) are women.Of the participants, 78% (63 players) reported having sustained at least one injury. Based on the location of injuries, the most affected area was the shoulder, with 17% (14 cases). Regarding the types of injuries, sprains showed a prevalence of 18% (15 cases), followed by muscle injuries at 15% (12 cases).Additionally, 60% of the injuries (48 cases) were of traumatic origin, resulting from direct impacts or common accidents in this contact sport. It was observed that an increased number of training hours significantly raises the risk of non-traumatic injuries.